ETHICAL CHALLENGES IN THE CONTEXT OF ARTIFICIAL INTELLIGENCE - Dr. Mario González Arencibia; Lic. Dagmaris Martínez Cardero (IJRDO -Journal of Computer Science Engineering, 2020)
The importance of the treatment of the subject associated with the malicious use of the results of Artificial Intelligence, is guiding the debate of studies from academic institutions, for its negative implications for society. In this sense, the purpose of this research is to reflect on the ethical dilemmas of technological developments in the framework of the Artificial Intelligence.  To this end, the research question is: How to eliminate the risks of malicious use of technological development in the field of Artificial Intelligence?  The study makes it possible to identify the critical points that are affecting society from technological applications, and to present the debate around their solutions. The conclusion of the research is that in the context of technological developments, the solution to ethical dilemmas is not only a technical problem, but requires a socially defined construction, and this is determined by the fact that digital systems, in the plane of their development and developers goes beyond their algorithms.